Natural Language Understanding - Allen, James (Noida, India Pearson, 2007)
Delivering coverage of semantic discourse and context, this book provides detailed and extensive examples of each technique it describes. It uses a uniform notation for all different algorithm techniques. This revised edition has chapters on statistically-based techniques and speech processing.
Include Appendices, Bibliography and Index.
Keywords: Artificial intelligence -- Language and logic -- Programming languages (Electronic computers)--Semantics